EEG-based methods for recovery prognosis of patients with disorders of consciousness: A systematic review. (December 2022) - Ballanti, Sara; Campagnini, Silvia; Liuzzi, Piergiuseppe; Hakiki, Bahia; Scarpino, Maenia; Macchi, Claudio; Oddo, Calogero Maria; Carrozza, Maria Chiara; Grippo, Antonello; Mannini, Andrea
Graphical abstract: Highlights: Simpler experimental setups for EEG recording were preferred (i.e., 10–20 International System and reduced number of electrodes). Qualitative and quantitative features were equally investigated but they are rarely studied together. The adoption of robust, generalisable, and validated methods for DoC prognosis is lacking and great heterogeneity exists among methods. Abstract: Objective: Disorders of consciousness (DoC) are acquired conditions of severely altered consciousness. Electroencephalography (EEG)-derived biomarkers have been studied as clinical predictors of consciousness recovery. Therefore, this study aimed to systematically review the methods, features, and models used to derive prognostic EEG markers in patients with DoC in a rehabilitation setting. Methods: We conducted a systematic literature search of EEG-based strategies for consciousness recovery prognosis in five electronic databases. Results: The search resulted in 2964 papers. After screening, 15 studies were included in the review. Our analyses revealed that simpler experimental settings and similar filtering cut-off frequencies are preferred. The results of studies were categorised by extracting qualitative and quantitative features. The quantitative features were further classified into evoked/event-related potentials, spectral measures, entropy measures, and graph-theory measures. Despite the variety of methods, features from all categories, including qualitative ones, exhibited significant correlations with DoC prognosis. Moreover, no agreement was found on the optimal set of EEG-based features for the multivariate prognosis of patients with DoC, which limits the computational methods applied for outcome prediction and correlation analysis to classical ones. Nevertheless, alpha power, reactivity, and higher complexity metrics were often found to be predictive of consciousness recovery. Conclusions: This study's findings confirm the essential role of qualitative EEG and suggest an important role for quantitative EEG. Their joint use could compensate for their reciprocal limitations. Significance: This study emphasises the need for further efforts toward guidelines on standardised EEG analysis pipeline, given the already proven role of EEG markers in the recovery prognosis of patients with DoC.